Desenvolvimento de cartilha com orientações sobre os cuidados com a pele de pessoas com radiodermite - Scienza, Ana Paula Machado (Universidade do Vale do Rio dos Sinos, 2023)
INTRODUCTION: radiodermatitis is a skin lesion resulting from radiotherapy, caused by the action of ionizing radiation on tissues, characterized as a side effect of cancer treatment. OBJECTIVES: to develop and validate a booklet with guidance on skin care for people with radiodermatitis. METHOD: methodological study, developed in three stages: 1) narrative review of the literature on skin care for people with radiodermatitis, aiming to support the development of the booklet content; 2) development of the booklet; 3) validation of the booklet with expert judges. In Stage 1, for the narrative review, the descriptors used: Radiodermatitis AND Guidelines. The searches were carried out on the Virtual Health Library portal, on Business Source Complete, on National Library of Medicine and on Google Scholar, without language limitations. In Stage 2, the construction of the content was supported by the results of the narrative review. In Stage 3, the booklet was validated by expert judges, all of whom were healthcare professionals: a dermatologist and stomal therapist nurses who worked in direct care for patients with radiodermatitis. The recruitment of participants took place using the snowball technique. An online form was used to collect data. Analysis using the Content Validity Index. RESULTS: Stage 1, six studies were analyzed and the categories emerging from the narrative literature review were: skin hygiene in the area receiving treatment; prevention against skin trauma; skin care in day-to-day radiotherapy treatment; and topical treatment. Stage 2 consisted of the development of the booklet, which consisted of 6 chapters in 39 pages. Pastel tones were used for the drawings and graphic art, seeking to give patients peace of mind. Stage 3 consisted of 14 expert judges in the health field, most of them nurses. The Content Validation Index was used to evaluate the educational technology developed. The booklet obtained an overall and satisfactory index of 96.5%. Domain 1 (objectives) obtained a score of 94.68%; domain 2 (structure), 98%; and domain 3 (relevance), 97.1%. CONCLUSION: finally, it is understood that the educational technology developed will contribute to empowering the self-care of patients and their caregivers. In addition to this, it also presents itself as an innovation in pharmaceutical assistance, opening new horizons and possibilities, adding technical knowledge, scientific basis and care provided both to the individual needs of people undergoing cancer treatment and in the area of radiotherapy.
Keywords: Radiodermite; Educação em saúde; Tecnologia educacional; Farmácia; Enfermagem; Radiodermatitis; Health education; Educational technology; Pharmacy; Nursing; ACCNPQ::Ciências da Saúde::Enfermagem